Clinical Profile and Outcome of COVID-19 in 250 Kidney Transplant Recipients: A Multicenter Cohort Study From India. Issue 4 (April 2021) - Kute, Vivek B.; Bhalla, Anil K.; Guleria, Sandeep; Ray, Deepak S.; Bahadur, Madan M.; Shingare, Ashay; Hegde, Umapati; Gang, Sishir; Raju, Sreebhushan; Patel, Himanshu V.; Jain, Siddharth; Godara, Suraj; et al.
Abstract : Background: There is a scarcity of data on the consequences of coronavirus disease-19 (COVID-19) infections in kidney transplant recipients (KTRs) from emerging countries. Methods: Here, we present a cohort study of 13 transplant centers in India including 250 KTR (226 living and 24 deceased donors) with polymerase chain reaction-confirmed COVID-19 positivity from March 23, 2020, until September 15, 2020. We detailed demographics, immunosuppression regimen, clinical profile, treatment, and outcomes. Results: Median age of transplant recipients was 43 years, and recipients presented at a median of 3.5 years after transplant. Most common comorbidities (94%) included arterial hypertension (84%) and diabetes (32%); presenting symptoms at the time of COVID-19 included fever (88%), cough (72%), and sputum production (52%). Clinical severity ranged from asymptomatic (6%), mild (60%), and moderate (20%) to severe (14%). Strategies to modify immunosuppressants included discontinuation of antimetabolites without changes in calcineurin inhibitors and steroids (60%). Risk factors for mortality included older age; dyspnea; severe disease; obesity; allograft dysfunction before COVID-19 infection; acute kidney injury; higher levels of inflammatory markers including C-reactive protein, interleukin-6 level, and procalcitonin; chest X-ray abnormality, and intensive care unit/ventilator requirements. Overall patient mortality was 11.6% (29 of 250), 14.5% (29 of 200) in hospitalized patients, 47% (25 of 53) in intensive care unit patients, and 96.7% (29 of 30) in patients requiring ventilation. KTRs with mild COVID-19 symptoms (n = 50) were managed as outpatients to optimize the utilization of scarce resources during the COVID-19 pandemic. Conclusions: Mortality rates in COVID-19-positive KTR appear to be higher than those in nonimmunosuppressed patients, and high mortality was noted among those requiring intensive care and those on ventilator.